Recent Developments in Indonesia's Macro-economy and Trade, Q1-2018 - Kacaribu, Febrio (UI Scholars Hub, 2018)
This paper discusses Indonesia's macroeconomic and trade development in the first quarter of 2018. The macroeconomic data shows that the industrial growth was inhibited by regulatory regime inconsistency, while consumption growth still lagged overall GDP growth, and investment growth tended to rise. The trade data shows that the non-oil-and-gas commodities dominated its export, although the commodities terms-of-trade declined. Indonesia's imports were mostly used as raw and auxiliary materials for the input of domestic production. The data also reveals that the larger the firms, the stronger tendency that they have comparative advantage in capital-intensive commodities, and vice versa.